2007
DOI: 10.1111/j.1365-2982.2007.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonosphincteric electromyographic responses to sacral root stimulation: evidence for a somatosympathetic reflex

Abstract: The aim of the present study was to determine the effects of selectively stimulating the afferent fibres running in the dorsal sacral roots (S1, S2, S3) and the somatic (radial and sciatic) nerves on colonic and internal anal sphincter (IAS) electromyographic (EMG) activity in anaesthetized cats to try to understand how sacral nerve stimulation can improve fecal continence in human. Electrically stimulating the afferent fibres present in the sacral dorsal roots and somatic nerves inhibited the colonic spike po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 43 publications
0
35
0
3
Order By: Relevance
“…12 A recent study in cats also indicated that SNS may improve fecal continence by inducing an inhibition of electromyographic activity of the colon, probably via a somato-sympathetic reflex. 13 These results may help to explain how SNS improves fecal continence in patients in whom both anal sphincters are impaired.…”
Section: Discussionmentioning
confidence: 95%
“…12 A recent study in cats also indicated that SNS may improve fecal continence by inducing an inhibition of electromyographic activity of the colon, probably via a somato-sympathetic reflex. 13 These results may help to explain how SNS improves fecal continence in patients in whom both anal sphincters are impaired.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent work we have shown, in the cat, that stimulating the sacral spinal roots may improve fecal continence by enhancing internal anal sphincter electromyographic activity and by inhibiting colonic electromyographic activity via a somatosympathetic reflex. 19 We have also demonstrated that stimulating the somatic afferent fibers induces the same effects on colonic and internal anal activity. This somatosympathetic reflex may explain in part the positive effect of posterior tibial nerve stimulation on fecal incontinence.…”
Section: Discussionmentioning
confidence: 93%
“…Dans ces conditions, il était logique que les patients présentant une lésion anatomique du sphincter anal externe significative, soient considérés comme de moins bons candidats pour ce traitement. Actuellement, il semble plus probable que la stimulation sacrée améliore la continence anale en modulant la motricité colo-rectale [26] et/ou la sensibilité rectale [19] voire le contrôle cérébral des organes périnéaux [27]. Aussi, des études préliminaires [9,10,28,29] ont évalué l'efficacité de la stimulation sacrée chez les patients incontinents anaux présentant une lésion du sphincter anal externe.…”
Section: Tableau 2 Indications Et Contre-indications De La Stimulatiunclassified
“…Plusieurs études ont attiré l'attention sur une réduction de la motricité colique au cours de la stimulation sacrée [18,26,45,46]. Vitton et al, ont démontré une inhibition de la motricité colique par stimulation des racines dorsales sacrées chez le chat qui mettrait en jeu un réflexe somato-sympathique (stimulation des afférences pelviennes entraînant un effet médullaire avec activation du système sympathique sacrée) [26]. Chez l'homme, Michelsen et al ont observé une augmentation significative du transport rétrograde du colon gauche et une tendance à l'augmentation du temps de transit chez des patients incontinents anaux traités par stimulation des racines sacrés [18].…”
Section: Mécanismes D'action De La Stimulation Des Racines Sacréesunclassified